The Influence of Leadership Styles on Teacher Motivation and Student Achievement (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
This research paper explores the relationship between leadership styles employed by school principals and the motivation of teachers, ultimately investigating the impact on student achievement. The study will analyze different leadership styles (e.g., transformational, transactional) and their influence on teacher morale, job satisfaction, and instructional practices. The paper will then examine how these factors influence student engagement and academic performance.